Telaah Determinan Kejadian Hipertensi di Desa Sukamakmur Kecamatan Binjai Kabupaten Langkat - Hasibuan, Rapotan; Ramadhani, Fauziah; Nanda, Ajeng Husni; Dalimunthe, Dirayati Annisa; Nasution, Latifah Azmy; Syahfira, Ayunda; Safitri, Sintia; Ariska, Ayu; Adeliyani, Mega (Preventia: The Indonesian Journal of Public Health, 2020)
Arterial hypertension is highly prevalent in the elderly, adult andadolescent population. The results from a doctor's diagnosis in a population over 18 years of age in Indonesia found a hypertension prevalence rate of 8.4%. Sukamakmur is one of the villages in Binjai District, Langkat Regency, which has 59 people suffering from hypertension in 2019 and is one of the 3 biggest diseases in there. This study, therefore, aimed to determine the determinants of hypertension in Sukamakmur Village. This research was a quantitative analytic study with a cross sectional design with70 samples of 70 householders taken by purposive sampling. Univariate and bivariate (chi-square) statistical analyzes were performed by means of computerization. The findings of the study showed that the incidence of hypertension was 10%. However, there was no significant relationship between smoking habits (p=0.704, 95% CI=0.245-8.009), and age category (p=0.107, 95% CI=0.582-45.001) in the incidence of hypertension. People who experienced an increase in blood pressure were as many as 7 people (10%) and those who experienced an increase in blood sugar were as many as 3 people (4.3%). The results of this study were in accordance with village data which states that hypertension is higher than diabetes.